THE PROBLEMATIC OF SANDY LANDS IN PARANAVAI MUNICIPALITY –PR - Marcelo Eduardo Freres Stipp (Sociedade & Natureza)
The sandy lands are a process of scouring with sand forming a sandy area, which correspondsto a reworking of the sands due its constant mobility, involving the transformation of notsolids deposits is sandy areas. This work tried to establish the characterization of thisphenomenon of scouring with sand in a local level, occurring in arenaceous areas in theNortheast of the state of Paraná, specifically in the urban site of Paranavaí. It was also madean evaluation of the environmental degradation as well as different causes for what provokedthese sandy areas. Being an area with a high level of soil decomposition with the highwaysroutes crossing it, it was necessary, besides bibliographic data that allowed a theoretical basis,a research applied in order to supply subsides for future planning related to the spaceorganization. The evolution of the use and soil occupation in this area has been processedwithin an urban planning which considered by no account neither soil characteristic, thevegetation nor the predominant climate in that region. The mechanisms of region atmospherecirculation were analyzed, the alterations or attributes of the climate as well, aiming toidentify the genesis of the erosion sandy and possible time and space distribution. Initially, themain characteristics of the region were collected, components e processes working on the landmodel. It was observed how it worked and the use and occupation of the soil in past times andcurrently. During 2004, using the Environmental Fragility Letter, the areas of erosion wereidentified, ravines and strong erosion that compounds the first stages of the focused problem.The sandy land is a process that involves erosion, transport, e accumulation, meaning most oftimes the loosing of Biosphere productivity. For monitoring these risk areas some measuringcanes were made to measure the soil loss, which were used in several spots of erosion in theurban area in Paranavaí. The measurement happened in every two months for a year in sixdifferent pre-established spots through satellite image that turned it valid in the study field.All together, the pluviometrical levels were analyzed to be related to the soil losses. It wasobserved initially that the causes of these facts were reflection of inappropriate handling ofthe urban soil, and in second time it was noticed that it had a broaden reach, involving fromecological unbalance, to politics, social and economical interests. Among them; thestabilization of this sand scouring some suggestions were made: the plantation of some treesin specific seasons of the year which hold the best conditions for their developing, forinstance, during the Winter the temperature is lower and the insolation lower as well,consequently it provokes a higher level of soil humidity.